Calibration and Validation of a Seismic Damage Propagation Model for Interdependent Infrastructure Systems. Issue 3 (August 2013) - Wu, Jason; Dueñas-Osorio, Leonardo
Barring a few exceptions, most theoretical and computational models of lifeline system fragility and interdependent response to extreme events still lack calibration and validation relative to real events. This paper expands on this area by evaluating and calibrating a recently proposed Interdependence Fragility Algorithm ( IFA ) against field data observed after the 2010 Mw 8.8 offshore Maule, Chile, earthquake. This evaluation incorporates available and simulated properties of the Concepción and Talcahuano water and power networks to try to replicate their topology and seismic response, considering both direct damage and interdependent effects. The calibrated IFA predicts that the probabilities of exceeding the observed high connectivity losses of 0.70 (power) and 0.82 (water), if taken as limit states, are 97% and 72%, respectively. These predictions capture complex interdependent lifeline system responses reasonably well and reveal influential factors for IFA model accuracy and uncertainty reduction, enabling reliable planning, design, expansion, and maintenance of infrastructure systems in practice.